Gambaran Kejenuhan Asn Saat Mengikuti Tes Cat Potensi Di Srondol Pada Bulan Ramadhan - Fatimah Azzahra Putri Bachtiar; Khairani Zikrinawati; Ismi Nur Arifah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
This study aims to describe the boredom experienced by civil servants (ASN) during the CAT potential test held in Srondol during the month of Ramadan. Using a descriptive qualitative approach, data were collected through observation and interviews with nine participants. The findings revealed that most respondents experienced a high level of boredom triggered by time pressure, complex questions, technical issues, and physical fatigue due to fasting. This boredom significantly affected their concentration and cognitive performance during the test. The results highlight the importance of optimizing technical execution, psychological support, and test environment management, especially during special conditions such as the Ramadhan period.